Urgensi Ratifikasi The 2001 Stockholm Convention on Persistent Organic Pollutants bagi Indonesia - Wahyu Yun Santoso (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2009)
Pollution has become one of the most significant problems in the environmental issues. Aside the effect of the pollution, another substantial factor of pollution is the character of the pollutant. Among several pollutant substances in the world, there are twelve main persistent organic pollutants, which are still in large and freely mobilized in our environment. On November 2001, the United Nations Environmental Program has issued a convention about persistent organic pollutants. So many enthusiasms from the states about this progress, as well as Indonesia did. However, after more than seven years, Indonesia has not submitted the ratification paper of this convention. This paper aims to analyze and elaborate the issues behind this convention and the urgency of submitting the ratification of Indonesian government.